AUTO-GREEN A Fully Automated Greenhouse Monitoring and Control System Using Data Logging - Shilpa Lambor, Tanushri Bhuruk, Ritesh Pokarne, Nikita Punde, Mahalakshmi Phaldesai, Prachi Kumar (Mathematical Statistician and Engineering Applications, 2023)
Greenhouses provide a regulated environment in which plants can be cultivated effectively. However, temperature, humidity, soil moisture, light intensity, and soil pH are all crucial elements for plant growth. We use a sensor network for continuous monitoring and control of this system. The RTC DS1307 module records the greenhouse parameters and sends them to the SD Card, where they are saved with their appropriate timestamps. We can easily access this data in an Excel Sheet. This recorded data can be analysed based on which the functioning of each sensor will begin. The major goals of this project were to create a user-friendly UI design and an automated system. The prototype’s potential to monitor and regulate the greenhouse remotely, as well as diagnose the viability of the plants, was shown by the experimental findings. Farmers may use the smart prototype to get real-time remote measurement and sensing services.